Uji Beberapa Pestisida Nabati Terh¬adap Kejadian Penyakit Antraknosa Pada Cabai Rawit Hiyung Di Desa Tajau Landung - Juhratul Habibah; Dewi Fitriyanti; Elly Liestiany (www.ulm.ac.id, 2022)
Cayenne pepper is one of the most important vegetables in Indonesia. There are several varieties of cayenne pepper, one of which is hiyung cayenne pepper which is grown in Hiyung village. Hiyung chili is the hottest chili in South Kalimantan, one of the hiyung chili plant diseases that causes a decrease in yield is anthracnose caused by the fungus Colletotrichum sp. Chili planting continues throughout the season, chemical pesticides used continuously have a negative impact on consumers, the environment and pathogens. The solution is environmentally friendly control, some environmentally friendly vegetable pesticides, namely karamunting, harmai, and rhizomes (lemongrass, snd ginger and turmeric). developed as a biopesticide that is environmentally friendly and beneficial for farmers. This study aims to determine the effect of the application of several vegetable pesticides in inhibiting the incidence of anthracnose in chili hiyung. This research was conducted in Tajau Landung Village, Sungai Tabuk District, Banjar Regency, in June – November 2021. The study used a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications so that there were 20 experimental units. The treatments were control (sterile water), administration of biopesticides from karamunting leaves, administration of pesticides from kaloi leaves and administration of botanical pesticides from rhizomes (lemongrass, sand ginger and turmeric). The results showed that the application of several vegetable pesticides had an effect on the incidence of anthracnose.